The book of Mirdad the strange story of a monastery which was once called the ark - Naimy, Mikhail 1889-1988 (London Watkins Publishing, 2011)
This timeless allegorical tale tells of the visit of a mysterious stranger, Mirdad, to the remote mountain monastery, the Ark. The conclusion and indeed the message is that Mirdad's Ark is the Ark of Holy Understanding, which will carry humankind across another deluge, greater than Noah's when heaven will be revealed on Earth. Through dialogue of reflection and recollection in which he engages with his chief disciple, we are shown the perennial wisdom of Mirdad's teaching on universal issues, including love, money, life, death, repentance and old age
Keywords: Mysticism